2004
DOI: 10.1016/s1534-5807(04)00131-5
|View full text |Cite
|
Sign up to set email alerts
|

Skp2-Mediated Degradation of p27 Regulates Progression into Mitosis

Abstract: Although Skp2 has been thought to mediate the degradation of p27 at the G(1)-S transition, Skp2(-/-) cells exhibit accumulation of p27 in S-G(2) phase with overreplication. We demonstrate that Skp2(-/-)p27(-/-) mice do not exhibit the overreplication phenotype, suggesting that p27 accumulation is required for its development. Hepatocytes of Skp2(-/-) mice entered the endoduplication cycle after mitogenic stimulation, whereas this phenotype was not apparent in Skp2(-/-)p27(-/-) mice. Cdc2-associated kinase acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

35
323
3
4

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 340 publications
(365 citation statements)
references
References 55 publications
35
323
3
4
Order By: Relevance
“…p27 Kip1 expression was increased upon knockdown of Skp2. Other Cdk inhibitor proteins, p21 Cip1 and p57 Kip2 , are putative targets of the SCF Skp2 complex Spruck et al, 2001;Kamura et al, 2003;Nakayama et al, 2004); however, we observed only minor changes in expression of these proteins following Skp2 knockdown in WM793 (Figure 5b) and WM278 cells (data not shown). Furthermore, Skp2 knockdown did not alter STAT1 levels (Sledz et al, 2003), indicating that changes in p27 Kip1 levels were not owing to an interferon response (data not shown).…”
Section: Skp2 Is Required For Downregulation Of P27 Kip1 Levels In Mementioning
confidence: 47%
See 2 more Smart Citations
“…p27 Kip1 expression was increased upon knockdown of Skp2. Other Cdk inhibitor proteins, p21 Cip1 and p57 Kip2 , are putative targets of the SCF Skp2 complex Spruck et al, 2001;Kamura et al, 2003;Nakayama et al, 2004); however, we observed only minor changes in expression of these proteins following Skp2 knockdown in WM793 (Figure 5b) and WM278 cells (data not shown). Furthermore, Skp2 knockdown did not alter STAT1 levels (Sledz et al, 2003), indicating that changes in p27 Kip1 levels were not owing to an interferon response (data not shown).…”
Section: Skp2 Is Required For Downregulation Of P27 Kip1 Levels In Mementioning
confidence: 47%
“…Malek and co-workers showed that deficient proliferation in regenerating liver cells from Skp2 (À/À) mice was associated with a G1 arrest and lack of cyclin A induction (Kossatz et al, 2004). In contrast, Nakayama et al (2004) showed that mouse embryo fibroblasts derived from Skp2 (À/À) mice had decreased Cdk1 and Cdk2 activity and exhibited a defect in progression through G2/M. Future experiments will analyse the effect of Skp2 and Cks1 knockdown on different stages of the cell cycle in melanoma cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the phenotype of Skp2 -/-p27 -/-mice is not identical to that of p27 -/-mice. Although accumulation of p27 mainly contributes to the proliferation defect of Skp2 -/-MEFs, Skp2 appears to prevent the accumulation of p27 during S-G 2 rather than at the G 1 -S transition (Nakayama et al, 2004). We have now shown that the delay in G 1 -S progression induced by Skp2 depletion was normalized by the additional depletion of RASSF1A even in the presence of a high level of p27 (Figure 6c).…”
Section: Discussionmentioning
confidence: 64%
“…Skp2 regulates entry into S phase by mediating degradation of the Cdk inhibitor p27 (Reed, 2003). However, the observation that the phenotype of Skp2 -/-p27 -/-mice is similar but not identical to that of p27 -/-mice (Nakayama et al, 2004) suggests that, although p27 might be the main target of Skp2, Skp2 likely also mediates the ubiquitination of other substrates. We therefore investigated whether G 1 -S progression might be affected by Skp2-mediated degradation of RASSF1A.…”
Section: Skp2 Regulates the Antiproliferative And Antisurvival Functimentioning
confidence: 99%